2015
DOI: 10.3390/ijms160714464
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Interactions between Water Extractable Soil Organic Matter and Metal Cations (Cu(II), Eu(III)) Using Excitation-Emission Matrix Combined with Parallel Factor Analysis

Abstract: The objectives of this study were to evaluate the binding behavior of Cu(II) and Eu(III) with water extractable organic matter (WEOM) in soil, and assess the competitive effect of the cations. Excitation-emission matrix (EEM) fluorescence spectrometry was used in combination with parallel factor analysis (PARAFAC) to obtain four WEOM components: fulvic-like, humic-like, microbial degraded humic-like, and protein-like substances. Fluorescence titration experiments were performed to obtain the binding parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
1
5
0
1
Order By: Relevance
“…Furthermore, FA1, which reveals the highest fa value, was also characterized by the largest number of COOH groups, which Higher values of stability constants for fluorophores from the B area indicated a greater stability of connections of Zn ions with the structures of lower molecular weight, which is typical of FAs. These results correspond to the ones obtained by Wei et al [66]. They reported that stability constants of Cu(II) and Eu(III) binding by water extractable organic matter revealed higher values for the component typical for FAs than for the component typical of humic acids.…”
Section: Quantification Of the Fa-zn(ii) Binding Processsupporting
confidence: 91%
“…Furthermore, FA1, which reveals the highest fa value, was also characterized by the largest number of COOH groups, which Higher values of stability constants for fluorophores from the B area indicated a greater stability of connections of Zn ions with the structures of lower molecular weight, which is typical of FAs. These results correspond to the ones obtained by Wei et al [66]. They reported that stability constants of Cu(II) and Eu(III) binding by water extractable organic matter revealed higher values for the component typical for FAs than for the component typical of humic acids.…”
Section: Quantification Of the Fa-zn(ii) Binding Processsupporting
confidence: 91%
“…Fluorescence quenching titration was performed following the method of Wei et al (2015). Briefly, the DOM solutions were first diluted to give DOC concentrations of 9.9, 10.6, and 6.1 mg/L for JAS300, JAS500, and JAS70, respectively, in order to minimize the fluorescence innerfilter effect.…”
Section: Methodsmentioning
confidence: 99%
“…The arbitrary units of the EEMs were then normalized using the integrated area of the blank Milli-Q water Raman peak located at Ex = 350 nm. The PARAFAC modeling is described in detail elsewhere (Wei et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…This is demonstrated by the lowest stability constant value Log K HA,C3 = 3.63. In comparison,Wei et al (2015) reported two stability constants using synchronous fluorescence spectroscopy. Their constants at pH 6 are higher than found in our study : Log K 1 =5.51 and Log K 2 =5.60.…”
mentioning
confidence: 99%